Water-based emulsion type carbon fiber sizing agent and preparation method thereof

By using organic unsaturated anhydride and polypolyol graft modified epoxy resin, an aqueous emulsion carbon fiber sizing agent containing a variety of functional groups was prepared, which solved the unstable sizing rate and poor interfacial bonding of the existing sizing agents. The problem of this is to achieve excellent mechanical properties and good stability of composite materials.

CN119465646APending Publication Date: 2025-02-18CHANGZHOU INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411547940.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing carbon fiber sizing agents have problems such as unstable sizing rate, harmful to the equipment and the environment, and poor binding of carbon fiber to the resin interface.

Method used

Using organic unsaturated anhydride and polypolyol graft modified epoxy resin, an aqueous emulsion carbon fiber sizing agent containing a variety of functional groups was prepared. The resin is water-based through the principles of internal emulsion and external emulsion, and the epoxy is retained. Functional groups to increase the chemical bonding of carbon fibers to resins.

Benefits of technology

The interface bonding force between carbon fiber and thermoset epoxy resin is improved. The composite material produced has excellent mechanical properties, and the sizing agent has moderate particle size and good mechanical and chemical stability, which is suitable for safe storage and transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465646A_ABST
    Figure CN119465646A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of carbon fiber sizing agents, and particularly relates to a water-based emulsion type carbon fiber sizing agent and a preparation method thereof. The water-based emulsion type carbon fiber sizing agent is prepared from the following components in parts by weight: 30 to 80 parts of epoxy resin, 6 to 10 parts of polyalcohol, 0.5 to 1.5 parts of unsaturated organic acid anhydride, 1.2 to 6.0 parts of diethanol amine, 3 to 6 parts of dichloroethoxyethanol, 0.3 to 0.5 part of catalyst, 50 to 70 parts of solvent and 180 to 500 parts of deionized water. The sizing agent is a waterborne epoxy sizing agent, is good in stability and small in particle size, can improve the binding force between carbon fibers and an epoxy resin matrix, and facilitates subsequent deep processing of the carbon fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon fiber sizing agents, and particularly relates to an aqueous emulsion type carbon fiber sizing agent and a preparation method thereof. Background Art

[0002] Carbon fiber is an advanced functional material with high specific modulus and high specific strength. Compared with traditional materials, it has the characteristics of high strength and low density. Therefore, it is widely used in sports equipment, medical equipment, automobiles and ships, aerospace and other fields. However, carbon fiber is essentially a brittle material. It will be repeatedly squeezed, stretched, rubbed and other effects during the production and processing, which will inevitably lead to problems such as fiber breakage and increased hair volume. In order to overcome this series of problems, it is necessary to sizing it, which can enhance the processability of carbon fiber and improve the bonding force between carbon fiber and resin matrix. Carbon fiber sizing agents are generally divided into solvent-based and emulsion-based. Solvent-based sizing agents are made by dispersing the main body of slurry in solvent. Due to the volatility of solvents, the sizing rate of this sizing agent is unstable and it is easy to have adverse effects on production equipment, production environment and human health. It is no longer used in the market. Emulsion-based sizing agents are made by dispersing the main body of slurry in water with the help of emulsifiers. This sizing agent has a small particle size, good stability and stable sizing rate. It is the mainstream sizing agent type on the market.

[0003] Carbon fiber sizing agents have been developed in China for decades, among which water-based epoxy resin composite material sizing agents account for the majority, and the systems used are mostly epoxy resins and organic solvents. For example, patent CN103451951A mentions the use of acetone as a solvent to prepare carbon fiber sizing agents. In recent years, for environmental protection, the number of sizing agents using water as a solvent has gradually increased. CN105332285A mentions that epoxy resins can be modified to make water-based sizing agents using water as a solvent. However, this method has problems such as reduced epoxy functional groups and poor interface bonding between sizing carbon fibers and resins. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides an aqueous sizing agent for carbon fiber and a preparation method thereof. The sizing agent adopts organic unsaturated acid anhydride and polyol graft modified epoxy resin, and the prepared sizing agent component structure contains various functional groups such as carboxyl, hydroxyl, epoxy, unsaturated double bond, ether bond, ester bond, etc. The sized carbon fiber has good interface bonding force with various thermosetting epoxy resins, and the prepared composite material has more excellent mechanical properties.

[0005] The components of the aqueous sizing agent for carbon fiber provided by the present invention in parts by weight are:

[0006] 30-80 parts by weight of epoxy resin, 6-10 parts by weight of polyol, 0.5-1.5 parts by weight of unsaturated organic acid anhydride, 1.2-6.0 parts by weight of diethanolamine, 3-6 parts by weight of dichloroethoxyethanol, 0.3-0.5 parts by weight of catalyst, 50-70 parts by weight of solvent and 180-500 parts by weight of deionized water.

[0007] The preparation method of the water-based carbon fiber sizing agent specifically comprises the following steps:

[0008] (1) A certain amount of polyol is placed in a reaction kettle, and water is removed in a vacuum at 80° C. until no bubbles are generated; then, an unsaturated organic acid anhydride and the polyol are mixed in the reaction kettle, diluted with a solvent, and a catalyst is added to keep the viscosity of the system within a good range, and the temperature is raised to 80-120° C. under a nitrogen protective atmosphere, and the reaction is stirred for 5-8 hours to obtain a graft copolymer A.

[0009]

[0010] [1] Preparation formula of graft copolymer A

[0011] The polyols include, but are not limited to, polyester polyols, polytetramethylene glycol, polyoxypropylene polyols, polyethylene glycol, etc., preferably one or more combinations of polyester polyols or polyethylene glycol.

[0012] The unsaturated organic anhydride includes, but is not limited to, phthalic anhydride, benzoic anhydride, maleic anhydride, succinic anhydride, etc., preferably one or more combinations of phthalic anhydride or maleic anhydride.

[0013] The solvent includes, but is not limited to, NN dimethylformamide, toluene, xylene, etc., preferably NN dimethylformamide or toluene.

[0014] (2) 10 to 25% of the total amount of epoxy resin and diethanolamine are mixed and placed in a reaction kettle, a certain amount of solvent and catalyst are added, and the mixture is stirred and reacted at 80° C. for 4 to 6 hours to obtain copolymer B.

[0015]

[0016] [2] General formula for preparation of graft copolymer B

[0017] The epoxy resin is a low-viscosity epoxy resin with an average degree of polymerization of 0 to 15. The epoxy resin includes but is not limited to a mixture of one or two of SM828U, SM828N, SM618, and SM6101, preferably a combination of one or two of SM618 and SM6101.

[0018] The catalyst includes, but is not limited to, potassium persulfate, triphenylphosphine, potassium hydride, barium hydroxide or boron trifluoride, etc., preferably one or more combinations of potassium persulfate or triphenylphosphine.

[0019] The solvent includes but is not limited to ethanol, propylene glycol methyl ether, toluene, etc., preferably one or more combinations of propylene glycol methyl ether or toluene.

[0020] (3) The copolymer B and dichloroethoxyethanol were mixed and placed in a reaction kettle, and stirred for reaction at 80° C. for 0.5 to 1 hour to obtain a copolymer C.

[0021]

[0022] [3] General formula for preparation of graft copolymer C

[0023] The solvent includes but is not limited to ethanol, propylene glycol methyl ether, toluene, etc., preferably one or more combinations of ethanol or toluene.

[0024] (4) The graft copolymer C and the graft copolymer A (accounting for 50% of the total amount) are placed in a reaction kettle, and a quantitative catalyst and a solvent are added. The temperature is raised to 100-130° C. under a nitrogen protective atmosphere, and the reaction is stopped by stirring for 4-6 hours to obtain a copolymer D.

[0025]

[0026] [4] General formula for preparation of graft copolymer D

[0027] The catalyst includes, but is not limited to, potassium persulfate, triphenylphosphine, potassium hydride, barium hydroxide or boron trifluoride, etc., preferably one or more combinations of potassium persulfate or triphenylphosphine.

[0028] The solvent is propylene glycol methyl ether.

[0029] (5) Blending copolymer D and the remaining copolymer A with the remaining epoxy resin, raising the temperature to 60-70° C., gradually adding deionized water dropwise under high-speed stirring in a stirrer, stirring at 5000-8000 r / min for 1-2 hours, and finally obtaining a water-based sizing agent.

[0030] The amount of deionized water added can be calculated based on the concentration of the sizing agent. The concentration of the prepared sizing agent is 15-30wt%, preferably 20-25wt%.

[0031] The beneficial effects of the present invention are:

[0032] (1) The present invention introduces bisphenol A epoxy resin into the system. The resin has low viscosity and good process performance, so that the carbon fiber has good bonding strength with the thermosetting epoxy resin after sizing, and the obtained composite material has excellent mechanical properties.

[0033] (2) The present invention introduces unsaturated organic anhydrides into the system, so that unsaturated ester bonds exist in the structure of the sizing agent component. In this way, the epoxy groups and ester bonds in the sizing agent can combine with functional groups such as carboxyl groups on the surface of the carbon fiber, thereby improving the chemical bonding force between the carbon fiber and the resin matrix.

[0034] (3) The present invention introduces polyether alcohol into the system to solve the key technical difficulty of preparing water-based emulsions with epoxy resins, overcome the problems of difficult safe and stable production and application of solvent-based sizing agents and environmental protection, and has a very broad market application prospect.

[0035] (4) The sizing agent prepared by the present invention has a moderate particle size, good mechanical stability and storage stability, and is convenient for safe storage and transportation. The emulsifier used is a homemade emulsifier, which reduces the use of conventional surfactants, and the sizing agent and sized carbon fiber have excellent physical and chemical stability.

[0036] (5) The present invention combines the preparation principles of internal emulsification and external emulsification, and introduces appropriate hydrophilic groups on the main chain of the molecule through polyether alcohol to achieve partial internal emulsification; then, an amphiphilic epoxy resin is used as an emulsifier to perform external emulsification on the unmodified epoxy resin, thereby achieving the water-based nature of the entire resin, retaining the epoxy functional groups of the epoxy resin, so that the carbon fiber can have a stronger chemical bonding force with the resin matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 , H-NMR spectrum of polyether after modification (deuterated chloroform as solvent).

[0038] Figure 2 , Comparison of surface morphology of carbon fiber before and after sizing.

[0039] Figure 3 , particle size distribution of carbon fiber sizing agent.

[0040] Figure 4 , tensile strength diagram of carbon fiber multifilament.

[0041] Figure 5 , transverse tensile strength diagram of carbon fiber composite materials. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] Comparative Example 1

[0044] Comparative Example 1 is selected from the commercially available SP-2C water-based epoxy emulsion type carbon fiber sizing agent (produced by Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences).

[0045] Examples 1-20

[0046] (1): A certain amount of polyol is placed in a reaction kettle, and water is removed in a vacuum at 80°C until no bubbles are generated; then, an unsaturated organic acid anhydride and the polyol are mixed in a reaction kettle, diluted with a solvent so that the viscosity of the system is maintained in a good range, a catalyst is added, the temperature is raised to 100°C under a nitrogen atmosphere, and the mixture is stirred for reaction for 5 hours to obtain a graft copolymer A.

[0047] (2): 10-25% of the total amount of epoxy resin and diethanolamine are mixed and placed in a reaction kettle, a quantitative solvent and a catalyst are added, and the mixture is stirred and reacted at 80° C. for 4 hours to obtain copolymer B.

[0048] (3) The copolymer B and dichloroethoxyethanol were mixed and placed in a reaction kettle, and stirred for reaction at 80° C. for 0.5 hour to obtain a copolymer C.

[0049] (4): Graft copolymer C and 50% graft copolymer A are placed in a reaction kettle, and a certain amount of solvent and catalyst are added. The temperature is raised to 120° C. under a nitrogen atmosphere and stirred for 4 hours to stop the reaction, thereby obtaining copolymer D.

[0050] (5): A certain amount of copolymer D and the remaining copolymer A are blended with the remaining epoxy resin, the temperature is raised to 65° C., deionized water is gradually added dropwise under high-speed stirring in a stirrer, and the mixture is stirred at 5000 to 8000 r / min for 1 hour to finally obtain a water-based sizing agent.

[0051] In Examples 1 to 20, the raw material amounts for preparing copolymer A are shown in Tables 1 to 4, the raw material amounts for preparing copolymer B are shown in Table 5, the raw material amounts for preparing copolymer C are shown in Table 6, the raw material amounts for preparing copolymer D are shown in Table 7, and the raw material amounts for preparing the aqueous emulsion are shown in Table 8.

[0052] Table 1 Amount of raw materials used to prepare copolymer A

[0053]

[0054]

[0055] Table 2 Raw material amounts for preparing copolymer A

[0056]

[0057] Table 3 Raw material amounts for preparing copolymer A

[0058]

[0059] Table 4 Raw material amounts for preparing copolymer A

[0060]

[0061] Table 5 Raw material amounts for preparing copolymer B

[0062] Epoxy resin(g) Diethanolamine(g) Triphenylphosphine Ethanol(g) Example 1 4 1.2 1.3 25.5 Example 2 8 2.4 1.4 26.1 Example 3 10 3 1.5 27.2 Example 4 20 6 1.8 32 Example 5 15 4.5 1.6 29

[0063] Table 6 Amount of raw materials used to prepare copolymer C (copolymer B is prepared in Example 5)

[0064] Copolymer B(g) Dichloroethoxyethanol(g) Example 1 13.61 3.78 Example 2 14.86 4.12 Example 3 15.83 4.39 Example 4 19.03 5.28 Example 5 17.43 4.84

[0065] Table 7 Raw material amounts for preparing copolymer D (copolymer A and copolymer C are prepared in Example 5)

[0066] Copolymer A(g) Copolymer C(g) Triphenylphosphine Propylene glycol methyl ether Example 1 3 17 0.13 25.3 Example 2 3.5 18 0.14 26.15 Example 3 4 19 0.15 27.2 Example 4 4.5 20 0.18 23.4 Example 5 5 21 0.16 29.6

[0067] Table 8 Amount of raw materials used to prepare sizing agent (copolymer A and copolymer D are prepared in Example 5)

[0068] Copolymer A(g) Copolymer D(g) Epoxy resin(g) Deionized water (g) Example 1 3 20 30 180 Example 2 3.5 20 40 240 Example 3 4 20 50 300 Example 4 4.5 20 60 360 Example 5 5 20 70 420

[0069] Sizing agent emulsion performance test:

[0070] The sizing agents prepared in the comparative example and Examples 1 to 5 were injected into the sizing tank of the high-performance single-filament bundle sizing simulation test device, and the unsized carbon fibers were immersed in the sizing tank at a uniform speed. After being dried in a hot air drying oven, they were wound up using an automatic winding machine to prepare sized carbon fibers.

[0071] The particle size and particle size distribution index of the sizing agent were tested using a Malvern Zetasizer dynamic light scattering instrument.

[0072] The physical stability of the sizing agent is qualitatively characterized by whether it is stratified and whether precipitation is produced after centrifugation. 30g of the sizing agent is centrifuged at 3000 rpm for 30 minutes to observe whether it is obviously stratified. If there is no obvious stratification, the weight of the bottom precipitate is weighed. The precipitate weight is less than 50mg, which is excellent; the precipitate weight is 50-100mg, which is medium, and the precipitate weight is greater than 100mg, which is poor. The less the precipitation, the better the physical stability.

[0073] The chemical stability of the sizing agent is quantitatively characterized by the pH applicable range. Different pH buffers are added to 50g of the sizing agent. If precipitation occurs, it indicates that the pH is not applicable. The larger the pH applicable range, the better the chemical stability.

[0074] Table 9 Sizing agent emulsion performance test data

[0075] Particle size (nm) Particle size distribution index Centrifugal sedimentation volume (mg) pH range Comparative Example 1 251 0.7 76.8 3~11 Example 1 470 1.3 148.5 1~14 Example 2 400 1.2 135.6 1~14 Example 3 252 0.7 77.3 1~14 Example 4 181 0.6 65.7 1~14 Example 5 277 0.7 79.2 1~14

[0076] Table 10 Interface shear performance data of carbon fiber monofilament after sizing

[0077] Interface shear strength (MPa) Comparative Example 1 59 Example 1 62 Example 2 69 Example 3 53 Example 4 62 Example 5 58

[0078] The H-NMR spectrum of the polyether alcohol modified product obtained in step (1). Wherein a and b are the characteristic peaks of CH on the unsaturated double bond generated by the esterification reaction of polyethylene glycol monomethyl ether with unsaturated organic acid anhydride; c is the characteristic peak of CH on the new ether bond generated by the esterification reaction of polyethylene glycol monomethyl ether with unsaturated organic acid anhydride; d and e are the characteristic peaks of CH on the polyether chain segment; f is the characteristic peak of the three hydrogen atoms on the methoxy group.

[0079] Figure 2 The following are surface morphology comparisons of carbon fiber before and after sizing. Figure (a) shows the surface morphology of unsized carbon fiber. It can be seen that the surface of unsized carbon fiber is relatively rough and has many longitudinal grooves on the surface. These are surface defects caused by the process in the production process of carbon fiber precursor. Figure (b) shows the surface morphology of carbon fiber after sizing with a homemade sizing agent. It can be seen that the surface defects of carbon fiber after sizing with a homemade sizing agent are significantly reduced. This is because the sizing agent emulsion particles fill the grooves on the surface of the carbon fiber, making the surface of the carbon fiber smoother, and forming a protective film on the surface of the carbon fiber, which improves the subsequent processability of the carbon fiber.

[0080] Figure 3 This is the particle size distribution of the carbon fiber sizing agent. It can be seen from the figure that the average particle size of the sizing agent is 185nm, which is relatively small. During the sizing process, the emulsion particles of the sizing agent can be well penetrated into the carbon fiber tow, making the carbon fiber sizing uniform.

[0081] Figure 4 is the tensile strength of carbon fiber multifilament. It can be seen from the figure that the transverse tensile strength of the carbon fiber composite material without sizing is 220.1MPa, and the transverse tensile strength of the carbon fiber composite material after sizing with a sizing agent is 258.87MPa. Since the sizing agent on the surface of the carbon fiber contains more epoxy groups, more chemical bonds can be generated after curing with the resin, which significantly improves the tensile strength of the carbon fiber multifilament.

[0082] Figure 5 is the transverse tensile strength of the carbon fiber composite material. It can be seen from the figure that the transverse tensile strength of the carbon fiber composite material without sizing is 23.64MPa, and the transverse tensile strength of the carbon fiber composite material after sizing with a sizing agent is 50.50MPa. Due to the meshing effect of the carbon fiber surface and the resin matrix and the chemical bonding force between the sizing agent and the resin matrix, the transverse tensile strength of the carbon fiber composite material is significantly improved.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aqueous emulsion type carbon fiber sizing agent, characterized in that: The sizing agent is composed of 30 to 80 parts by weight of epoxy resin, 6 to 10 parts by weight of polyol, 0.5 to 1.5 parts by weight of unsaturated organic acid anhydride, 1.2 to 6.0 parts by weight of diethanolamine, 3 to 6 parts by weight of dichloroethoxyethanol, 0.3 to 0.5 parts by weight of catalyst, 50 to 70 parts by weight of solvent and 180 to 500 parts by weight of deionized water.

2. The aqueous emulsion type carbon fiber sizing agent according to claim 1, characterized in that: The epoxy resin is one of SM828U, SM828N, SM618, and SM6101, or a mixture of two of them.

3. The aqueous emulsion type carbon fiber sizing agent according to claim 1, characterized in that: The polyols are polyester polyols, polytetramethylene glycol, polyoxypropylene polyol and polyethylene glycol.

4. The aqueous emulsion type carbon fiber sizing agent according to claim 1, characterized in that: The unsaturated organic acid anhydrides are phthalic anhydride, benzoic anhydride, maleic anhydride and succinic anhydride.

5. A method for preparing the aqueous emulsion type carbon fiber sizing agent according to claim 1, characterized in that: The preparation method steps are as follows: (1) placing a polyol in a reaction kettle and removing water in a vacuum at 80° C. until no bubbles are generated; then mixing the unsaturated organic acid anhydride and the polyol in a reaction kettle, diluting with a solvent, adding a catalyst, heating to 80 to 120° C. under a nitrogen atmosphere, stirring and reacting for 5 to 8 hours, and then stopping to obtain a graft copolymer A; (2) 10 to 25% of the total amount of epoxy resin and diethanolamine are mixed and placed in a reaction kettle, a solvent and a catalyst are added, and the mixture is stirred and reacted at 80° C. for 4 to 6 hours to obtain a copolymer B; (3) mixing copolymer B and dichloroethoxyethanol and placing them in a reaction kettle, stirring and reacting at 80° C. for 0.5 to 1 hour to obtain copolymer C; (4) placing the graft copolymer C and 50% of the total amount of the graft copolymer A in a reaction kettle, adding a catalyst, heating to 100-130° C. under a nitrogen atmosphere, stirring for 4-6 hours to stop the reaction, and obtaining a copolymer D; (5) Blending copolymer D and the remaining copolymer A with the remaining epoxy resin, heating to 60-70° C., adding deionized water dropwise under high-speed stirring in a stirrer, stirring at 5000-8000 r / min for 1-2 hours, and finally obtaining a water-based sizing agent.

6. The method for preparing the aqueous emulsion type carbon fiber sizing agent according to claim 5, characterized in that: In step (2), the solvent is ethanol, propylene glycol methyl ether, or toluene.

7. The method for preparing the aqueous emulsion type carbon fiber sizing agent according to claim 5, characterized in that: In step (2), the catalyst is potassium persulfate, triphenylphosphine, potassium hydride, barium hydroxide or boron trifluoride.

8. The method for preparing the aqueous emulsion type carbon fiber sizing agent according to claim 5, characterized in that: In step (4), the catalyst is potassium persulfate, triphenylphosphine, potassium hydride, barium hydroxide or boron trifluoride, and its amount is 0.5% of the total mass of the graft copolymer C and the graft copolymer A.

Citation Information

Patent Citations

  • Preparation method of carbon fiber sizing agent

    CN103451951A

  • Water-borne sizing agent for carbon fiber and preparation method and sizing method thereof

    CN105332285A